Mineral deformation and subglacial processes on ice-bedrock interface of Hailuogou Glacier - Liu GengNian; Chen YiXin; Zhang Yue; Fu HaiRong (Chinese Science Bulletin, 2009)
Hailuogou Glacier is located in a warm and humid maritime environment. It is large and moves very fast. The bottom of the glacier slides intensively and the temperature at the bottom approaches the pressure melting point. Therefore, there are abundant melting water and debris which act as effective "grinding tools" for glacial abrasion. Polarizing microscope is used to observe the mineral deformation characteristics on the ice-bedrock interface. It is found that feldspar, quartz, hornblende and biotite are exposed to deformation, fracture and chemical alteration to various extents. Bending deformation is common for biotite, due to their lattice characteristics, and the bending orientations are mostly the same as the glacier flow. Bending deformation also occurs in a few hornblendes. High-angle tension fracture and low-angle shear fracture are common for quartz and feldspar, some of them are totally crushed (mylonizations) due to their rigidity. Thus, all the abrasion, quarrying, subglacial water action and subglacial dissolution processes at the bottom of the glacier are verified at the micro-scale level. Mineral deformation and fracture are the basic subglacial erosion mechanisms. The abrasion thickness is 30-90 mu m for each time and the average is 50 mu m. Most of the debris are silt produced by glacial abrasion. The extent of mineral deformation and fracture decreases drastically downwards beneath the bedrock surface. The estimated erosion rate is about 2.2-11.4 mm/a, which is similar to that of other maritime alpine glaciers, smaller than that of large-scale piedmont glaciers in Alaska (10-30 mm/a), and larger than that of continental glaciers (0.1-1.0 mm/a). The type and size of a glacier are the main factors that influence its erosion rate. Multidisciplinary Sciences SCI(E) 1 ARTICLE 18 3318-3325 54